Ginsenoside Rg3 Ameliorates Stress of Broiler Chicks Induced by Escherichia coli Lipopolysaccharide - Bi, Shicheng; Qu, Yiwen; Shao, Jianjian; Zhang, Jianrong; Li, Weihao; Zhang, Li; Ni, Jingxuan; Cao, Liting (Frontiers in Veterinary Science, 2022)
In broiler chicks, Escherichia coli lipopolysaccharide is a prominent cause for inflammatory damage and loss of immune homeostasis in broiler chicks. Ginsenosides have been shown to have anti-inflammatory and antioxidant effects. However, it has not been demonstrated that ginsenosides protect broiler chicks against stress induced by Escherichia coli lipopolysaccharide challenge. The aim of this is to investigate the protective effect of ginsenosides Rg1, Re, and Rg3 on Escherichia coli lipopolysaccharide-induced stress. Our results showed that Rg3 ameliorated growth inhibition and fever, as well as decreased the production of stress-related hormones in broilers with stress. The protective effect of Rg3 on the stressed chicks may be largely mediated by regulating inflammatory response and oxidative damage. Moreover, real-time quantitative-polymerase chain reaction (RT-qPCR) results demonstrated that Rg3 upregulated mRNA expression of mTOR, HO-1, and SOD-1. These results suggested that ginsenoside Rg3 and ginsenoside products contains Rg3 deserve further study for the control of immunological stress and inflammation in broiler chicks.